Malassezia pachydermatis up-regulates AhR related CYP1A1 gene and epidermal barrier markers in human keratinocytes. (15th February 2018) - Buommino, Elisabetta; Baroni, Adone; Papulino, Chiara; Nocera, Francesca Paola; Coretti, Lorena; Donnarumma, Giovanna; De Filippis, Anna; De Martino, Luisa
Abstract: Cytochrome P450 CYP1A1 and CYP1B1 enzymes are regulated by the aryl hydrocarbon receptor (AhR), a transcription factor activated by a variety of ligands among which Malassezia metabolites. In this study, we analyzed the modulation of CYP1A1, CYP1B1, and AhR in human keratinocytes infected with different strains of Malassezia pachydermatis, as well as the upregulation of some genes involved in the epidermal homeostasis. We demonstrated that all the strains induced AhR activation and its nuclear translocation in HaCaT cells infected for 24 h, compared to untreated cells. The expression of CYP1A1 and CYP1B1, prototypical markers of the AhR signaling pathway, were upregulated with the level of CYP1A1 mRNA approximately 100-fold greater than that for CYP1B1. Filaggrin, involucrin, and TGaseI, proteins involved in epidermal differentiation, were all modulated by Malassezia pachydermatis strains, with the strongest induction observed for filaggrin. By contrast, quinone oxidoreductase 1 (NQO1), which is part of the antioxidant defense system involved in detoxification, was not modulated in our experimental model. In conclusions, our findings suggest that Malassezia pachydermatis infection of human keratinocytes induces activation of the AhR, and increases the expression of its responsive genes and markers of epidermal differentiation, paving the way for occurrence/exacerbation of pathological skin conditions.